Exploration of science teacher identity construction through various lived experiences - Ari Dhinansah Herdhiyani; Endang Purwaningsih; Arif Hidayat (Momentum: Physics Education Journal, 2024)
Identity is the construction of interpretations of life experiences in certain contexts, resulting in self-understanding. This research, with a single case study design, aims to explore the identity of science teachers in various contexts of Figured Worlds. The research participant is a science teacher named Yuni (pseudonym), who has a background in Physics Education. Data were collected through two semi-structured interviews. The results revealed how Yuni interpreted science-related life experiences in Figured Worlds to construct her identity. The researchers concluded that although, throughout Yuni's experience, she was not interested in becoming a teacher, she was able to become an outstanding teacher through her scientific papers.